Affects and Extractivism on La isla de Fushía de Irma del Águila - Di Benedetto, Matías (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This work investigates the literary representation of affections through a set of compositionalresources such as fragmentation and narrative discontinuity in the novel La isla de Fushíaby Irma del Águila. Through its intertextual relations with the works of Mario Vargas LlosaLa casa verde [The Green House] and Historia secreta de una novela, we highlight how toaddress political concerns related to the environmental (and affective) impact of extractiveprocesses. We are interested in reviewing the alternation between affection and extractivism,based on the deployment of a cartography of the Amazonian territory while taking a distancefrom the literary regionalism of the beginnings of the 20th century. So, the idea is to revealhow the inclusion of an affective and geographic map has the purpose of evoking personaland colonial traumas, the recovery of the voices of the jungle, more about the testimonyabout the subjection to the conditions imposed by the influence of the Capitalocene that of itsrepresentation in so much vernacular exoticism.